Synthetic methods in the poetry of Saudi poet Jassim bin Mohammed Al-Sa Through Diwan: The Three Parts of Complete Poetry Works - Alemrani, Aryaf Faraj (Journal of Arabic Language Sciences and Literature, 2024)
This study deals with the compositional methods in the poetry of the Saudi poet Jassim bin Muhammad al-Sahih, through the Divan of the Three Parts of Poems of Complete Poetic Works; In order to identify these methods consisting of the interrogative style, the order, the prohibition, and the call, and their meanings and indications in his poetry, and to achieve the objectives of the study, the researcher will use the descriptive approach in tracking phenomena and methods, and the analytical and inductive approach in extracting the purposes from the evidence, and the analysis and linking that this requires. each witness in its own context, it is the most appropriate approach for this study, in order to gain knowledge of all aspects related to the subject, and the researcher will depend on the sources and references related to the subject of the study. The study reached several results, the most important of which are:1- The poet's poems are rich in linguistic structures and styles of all kinds.2- She explained that his poetry is characterized by a strong literary language that is characterized by its inclusion of these styles.3- The poet intensified his poetic language with phraseological and stylistic patterns through which he expressed his thoughts, emotions and feelings.
Keywords: compositional styles; poetry; Jassim Al-Sahih